Genetically Engineered Elastin-based Biomaterials for Biomedical Applications - Santos, Mercedes; Serrano-Dúcar, Sofía; González-Valdivieso, Juan; Vallejo, Reinaldo; Girotti, Alessandra; Cuadrado, Purificación; Arias, Francisco J. (Current Medicinal Chemistry, 2019)
Protein-based polymers are some of the most promising candidates for a new generation of innovative biomaterials as recent advances in genetic-engineering and biotechnological techniques mean that protein-based biomaterials can be designed and constructed with a higher degree of complexity and accuracy. Moreover, their sequences, which are derived from structural protein-based modules, can easily be modified to include bioactive motifs that improve their functions and material-host interactions, thereby satisfying fundamental biological requirements. The accuracy with which these advanced polypeptides can be produced, and their versatility, self-assembly behavior, stimuli-responsiveness and biocompatibility, means that they have attracted increasing attention for use in biomedical applications such as cell culture, tissue engineering, protein purification, surface engineering and controlled drug delivery. The biopolymers discussed in this review are elastin-derived protein-based polymers which are biologically inspired and biomimetic materials. This review will also focus on the design, synthesis and characterization of these genetically encoded polymers and their potential utility for controlled drug and gene delivery, as well as in tissue engineering and regenerative medicine.
Keywords: Drug delivery